2016
DOI: 10.1016/j.ymgme.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model system for neuronal dysfunction in Fabry disease

Abstract: Fabry disease is a glycosphingolipid storage disorder that is caused by a genetic deficiency of the enzyme alpha-galactosidase A (AGA, EC 3.2.1.22). It is a multisystem disease that affects the vascular, cardiac, renal, and nervous systems. One of the hallmarks of this disorder is neuropathic pain and sympathetic and parasympathetic nervous dysfunction. The exact mechanism by which changes in AGA activity result in change in neuronal function is not clear, partly due to of a lack of relevant model systems. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Models of Fabry disease have been developed in human embryonic kidney cells HEK and human neuroblastoma cells differentiated into cholinergic-like neurons. 81 , 99 In both cell types, α-Gal A RNA expression was knocked down using short hairpin RNAs. Both studies observed accumulation of Gb3 deposits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Models of Fabry disease have been developed in human embryonic kidney cells HEK and human neuroblastoma cells differentiated into cholinergic-like neurons. 81 , 99 In both cell types, α-Gal A RNA expression was knocked down using short hairpin RNAs. Both studies observed accumulation of Gb3 deposits.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies observed accumulation of Gb3 deposits. 81 , 99 A-Gal A–deficient HEK cells exhibited an altered sodium channel function, and the neuroblastoma cells showed differences in proliferation and release of the neurotransmitter acetylcholine. 81 These cells are relatively easy to culture and manipulate; however, both HEK and neuroblastoma cells are phenotypically different from native sensory neurons and therefore are likely limited in modeling sensitization mechanisms in sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies also pointed to an altered sympathetic innervation as well as noradrenergic/cholinergic neurotransmitter coding in Fabry disease (Stemper and Hilz, 2003;Jardim et al, 2006;Kaneski et al, 2016). In this context, an in vitro model for neuronal dysfunction in Fabry disease suggested insufficiency of cholinergic function (Kaneski et al, 2016).…”
Section: The Role Of the Dysfunctional Endothelial No Metabolism In Fabry Diseasementioning
confidence: 99%
“…Interestingly, studies also pointed to an altered sympathetic innervation as well as noradrenergic/cholinergic neurotransmitter coding in Fabry disease (Stemper and Hilz, 2003;Jardim et al, 2006;Kaneski et al, 2016). In this context, an in vitro model for neuronal dysfunction in Fabry disease suggested insufficiency of cholinergic function (Kaneski et al, 2016). It was also shown that during local and whole-body heating, acetylcholine is released, inducing cutaneous vasodilation, presumably via NO synthase pathways (Shibasaki et al, 2002;Holowatz et al, 2005).…”
Section: The Role Of the Dysfunctional Endothelial No Metabolism In Fabry Diseasementioning
confidence: 99%